Eastern Approaches: Interball in the International Solar‐Terrestrial Program - D. G. Sibeck (Perspectives of Earth and Space Scientists)
Abstract Progress in space plasma physics, or Heliophysics, necessarily requires the combined efforts of scientists in many nations employing observations from many spacecraft and ground‐based observatories. This article describes some of my efforts to integrate the Soviet missions Interball‐1 and ‐2 missions into the International Solar Terrestrial Physics program during the 1990's, with a focus on studies concerning the interaction of the solar wind with the Earth's dayside magnetosphere.